2021
DOI: 10.3390/jcm10235638
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Distribution of Dental Biofilm after Insertion of Fixed Orthodontic Appliances

Abstract: Good oral hygiene is an important factor in oral and general health, especially in orthodontic patients, because fixed appliances might impede effective oral hygiene and thus increase the risks of tooth decay, periodontal disease and general health complications. This study investigated the impact of fixed orthodontic appliances on the distribution of dental biofilm in teenagers. Supragingival plaque was assessed at T0, T1 and T2. The distribution of the biofilm was analyzed. Approximal Plaque Index (API) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The Dd score in the RMD group showed that the level of demineralization was lower than that in the RMGIC group, although the results of EDI and Dd scores was not sufficient to diagnose demineralization on both groups after 3 months. Previous studies have found that various periodontal indices increased after 3 months of treatment, among which the increase in plaque index was the most obvious ( Kozak, Lasota & Chałas, 2021 ). In our study, compared to RMGIC, plaque accumulation was significantly inhibited by RMD, while no significant difference was observed on gingival index.…”
Section: Discussionmentioning
confidence: 97%
“…The Dd score in the RMD group showed that the level of demineralization was lower than that in the RMGIC group, although the results of EDI and Dd scores was not sufficient to diagnose demineralization on both groups after 3 months. Previous studies have found that various periodontal indices increased after 3 months of treatment, among which the increase in plaque index was the most obvious ( Kozak, Lasota & Chałas, 2021 ). In our study, compared to RMGIC, plaque accumulation was significantly inhibited by RMD, while no significant difference was observed on gingival index.…”
Section: Discussionmentioning
confidence: 97%
“…There are numerous publications in the literature on the effect of acrylic restorations on the adult population. Kozak et al studied the effect of fixed orthodontic appliances on the distribution of dental biofilm [ 18 ]. However, few studies in this area concern removable orthodontic appliances used by the youngest patients [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the oral cavity should be considered as a possible source of toxigenic Staphylococcus aureus strains, and thus a potential risk of cross-infection and dissemination to other sites in the body [8] . It is important to emphasize that some fixed components used in orthodontics (molar tubes, ceramic brackets, and elastomeric ligatures) were found to show high risks of causing periodontal disease [9] , because orthodontic appliances seem to be associated with a qualitative increase in the subgingival microbiota [10] and also with a frequent increase in the amount of supragingival plaque in the vestibular region of the teeth [11] .…”
Section: Introductionmentioning
confidence: 99%